Human Resources Capacity Development at the Jeneponto Regency Community and Village Empowerment Office - Ririn Anugrah Wahyul; Muh. Thahir Haning; Suryadi Lambali (IHSA Institute, 2024)
Human Resources capacity building is the process of improving the abilities, knowledge, skills, and attitudes of individuals and groups in an organization. The goal is to improve quality, productivity, and competitiveness in achieving certain goals. The purpose of this study was to determine and analyze Human Resource Capacity Development at the Jeneponto Regency Community and Village Empowerment Office. This research uses a type of qualitative research with a descriptive approach. Data collection techniques using observation instruments and in-depth interviews. With data analysis techniques, namely: Data condensation, Data Presentation and Conclusion Drawing. The results of this study indicate that the Jeneponto Regency Community and Village Empowerment Office should be appreciated for its continuous efforts in improving the quality of human resources through education and training, learning assignments, and promotions and awards. These efforts demonstrate the local government's commitment in realizing good and accountable village governance, as well as encouraging the progress and empowerment of village communities. With structured and sustainable efforts, the Jeneponto Regency Community and Village Empowerment Office can continue to improve the quality of human resources and realize quality, effective, and accountable village governance, for the progress and welfare of village communities